2022
DOI: 10.1002/rth2.12677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new bead‐based assay to measure levels of human tissue factor antigen in extracellular vesicles in plasma

Abstract: Background Circulating tissue factor (TF)‐expressing extracellular vesicles (EVs) are associated with thrombosis in several diseases, such as coronavirus disease 2019 (COVID‐19). Activity assays have higher sensitivity and specificity compared to antigen assays for measuring TF+ EVs in plasma. The MACSPlex Exosome Kit is designed to detect 37 exosomal surface epitopes, including TF, on EVs in plasma using various fluorescently labeled beads. The different EV‐bead complexes are detected by flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…We recently evaluated a new bead‐based assay called the MACSPlex Exosome kit to measure levels of human TF antigen on EVs in plasma. Unfortunately, in contrast to our in‐house activity assay, we found that the kit was not sensitive enough to detect the low levels of TF + EVs in plasma from LPS stimulated whole blood and plasma from patients with ovarian cancer 23 …”
Section: Measurement Of Tf + Evscontrasting
confidence: 61%
See 1 more Smart Citation
“…We recently evaluated a new bead‐based assay called the MACSPlex Exosome kit to measure levels of human TF antigen on EVs in plasma. Unfortunately, in contrast to our in‐house activity assay, we found that the kit was not sensitive enough to detect the low levels of TF + EVs in plasma from LPS stimulated whole blood and plasma from patients with ovarian cancer 23 …”
Section: Measurement Of Tf + Evscontrasting
confidence: 61%
“…Unfortunately, in contrast to our inhouse activity assay, we found that the kit was not sensitive enough to detect the low levels of TF + EVs in plasma from LPS stimulated whole blood and plasma from patients with ovarian cancer. 23 We and others developed similar in-house FXa generation assays that measure EVTF activity kinetically 9 or as an endpoint. 14 Briefly, EVs in plasma are pelleted by centrifugation and washed twice with buffer.…”
Section: Me a Surement Of Tf + E Vsmentioning
confidence: 99%
“…Blood samples were collected from patients with ovarian cancer using a protocol approved by the University of North Carolina at Chapel Hill Institutional Review Board (11-1201). Some of the ovarian cancer samples were used in a previous study [ 39 ]. Some of the trauma samples were used in previous studies [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the study used serum instead of plasma and added the labeled beads directly to the serum rather than isolating the EVs as recommended by the manufacturer. We evaluated the ability of the MACSPlex Exosome Kit to detect TFþ EVs in plasma [94]. We found that the kit was unable to distinguish between samples with or without TFþ EVs.…”
Section: Measurement Of Tf Protein On Evs Using a Bead Assaymentioning
confidence: 99%